Developing Generic Competences in Life Sciences: the untold story of the Makerere University College of Health Sciences in Uganda - Lazarus Nabaho (Universidad de Deusto, 2017)
Ordinarily, higher education should transform the student. Transformation refers to the development of high order subject and generic competences as a consequence of the university experience. The current discourse on generic competences, especially in the African context, focuses largely on the end (generic competences to be developed) rather than the means or process (how to develop the generic competences). Relatedly, the discussion on the subject treats generic competences as general and does not give insights into whether the priority attached to generic competences varies across disciplines. It is against this backdrop that the paper set out to identity the generic competences which are aligned with dental surgery and nursing education at Makerere University in Uganda. The paper further delved into the strategies for developing generic competences among medical students. Data for the paper was collected from dental surgery and nursing academics using interviews. The resultant data was analysed using thematic analysis. The findings revealed that problem solving, lifelong learning and interpersonal competences are aligned with life sciences. The utilitarian nature of life sciences, the rapidly changing mode of diseases and the attendant treatment options, and the highly social nature of the life sciences explicate this apparent alignment. The findings further revealed that the university employs three approaches to develop generic competences: problem-based learning, conducting generic course units, and role modelling. Therefore, it can be inferred that the generic competences to be developed on a particular academic discipline and the approaches used to develop them are a curriculum issue.